1998
DOI: 10.1021/jp980955s
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Investigation of Multiple Partitioning Sites in Aqueous and Reverse Micelles

Abstract: Our investigations seek to illustrate the use of fluorescence spectral deconvolution to characterize multiple partitioning sites for aromatic chromophores within aqueous and reverse micelles. The spatial distribution of solutes within micellar systems is dictated by a variety of noncovalent interactions. To probe for multiple partitioning microenvironments, we use the aromatic fluorophore Prodan with its extensive solubility in a range of media and its appreciable spectral sensitivity to the polarity of its su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(98 citation statements)
references
References 18 publications
10
86
1
1
Order By: Relevance
“…3) suggest that it is predominantly located at the C 12 E 5 /water boundary, but also shows (see short wavelength shoulder) some tendency to sit in a hydrocarbon rich region. Studies in reverse micelles using this probe also point to multiple partitioning sites [11,12].…”
Section: Resultsmentioning
confidence: 98%
“…3) suggest that it is predominantly located at the C 12 E 5 /water boundary, but also shows (see short wavelength shoulder) some tendency to sit in a hydrocarbon rich region. Studies in reverse micelles using this probe also point to multiple partitioning sites [11,12].…”
Section: Resultsmentioning
confidence: 98%
“…After comparing the separation of six arylacetophenones using three different surfactants with AOT, we think that AOT micelles were formed in FA solvent even though they were not as stable as the SDS micelles. Physicochemical studies and the use of AOT have been widely carried out [25,26] and are still continuing, so we believe in the near future the character of AOT aggregates in different solvents will be elucidated. Similar to the results for AOT, STDC also cannot form micelles in NMF or DMF solvents.…”
Section: Electrolyte and Surfactantmentioning
confidence: 99%
“…Our previous investigations of the fluorescence signature of prodan in various surfactant aggregates [13][14][15][16] suggest that several intermolecular forces influence probe distribution, including electrostatic interactions, hydrophobic interactions, and van der Waals forces. Specifically, for aqueous micelles, prodan may either (1) locate at the micellar surface via nonspecific weak dipole interactions with the surfactant headgroups; (2) interact with cationic surfactant headgroups through an electrostatic interaction of the aromatic pi electrons (a potential cation-pi interaction); or (3) incorporate with the nonpolar surfactant core via hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that prodan's solubility in a wide-range of solvents enables the distribution of this neutral probe into multiple microregions of aqueous micelles and reverse micelles. [13][14][15][16] Furthermore, a fluorescence signal that is simultaneously indicative of multiple locations results as a consequence of both the measurable fluorescence intensity of prodan in an extensive number of solvents and the sensitivity of the wavelength of maximum emission (l max ) to the polarity of prodan's environment. [13][14][15][16][17] For example, the emission maximum ranges from 402 nm in the nonpolar solvent cyclohexane to 522 nm in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation